2020
DOI: 10.1186/s12951-020-00658-7
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic bactericidal effect of low-frequency and low-intensity ultrasound combined with levofloxacin-loaded PLGA nanoparticles on M. smegmatis in macrophages

Abstract: Purpose: Tuberculosis (TB) is a highly infectious disease caused by Mycobacterium tuberculosis (Mtb), which often parasites in macrophages. This study is performed to investigate the bactericidal effect and underlying mechanisms of low-frequency and low-intensity ultrasound (LFLIU) combined with levofloxacin-loaded PLGA nanoparticles (LEV-NPs) on M. smegmatis (a surrogate of Mtb) in macrophages. Methods and results: The LEV-NPs were prepared using a double emulsification method. The average diameter, zeta pote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…In addition to the CTAB turbidimetric method for determining the effective connection of covalent bonds, a change in particle size from the nanometre to the micrometre scale also confirmed the effective connection of HA. 25 Although their particle size increased, the microbubbles remained smaller than red blood cells. HA affected the potential of the microbubbles, which is important for ensuring passage through the capillary network and engulfment by macrophages.…”
Section: Optimal Ha Loading Capacitymentioning
confidence: 99%
“…In addition to the CTAB turbidimetric method for determining the effective connection of covalent bonds, a change in particle size from the nanometre to the micrometre scale also confirmed the effective connection of HA. 25 Although their particle size increased, the microbubbles remained smaller than red blood cells. HA affected the potential of the microbubbles, which is important for ensuring passage through the capillary network and engulfment by macrophages.…”
Section: Optimal Ha Loading Capacitymentioning
confidence: 99%
“… 44 Xie et al also reported nano-formulated levofloxacin enhanced the killing M. smegmatis in macrophages under ultrasonic treatment. 45 However, these nano-formulated anti-tuberculosis agents delivered the drug to its target using a free passive movement and passive targeting strategy. More research has revealed that active targeting mechanisms are more effective for targeted drug delivery than passive targeting mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…We also speculate that the significant therapeutic effect may be related to the cavitation effect of ultrasound enhancing the permeability of cell membranes to promote drug uptakes. 45 , 50 The results from CLSM and flow cytometry ( Figure 6 ) analysis demonstrated that ultrasound facilitated the increased nanoparticle uptake by macrophage and BCG bacteria, implying that ultrasound can efficiently translocate the drug into the cell where the pathogens reside and replicate. Intracellular drug accumulation then promotes the bacterial uptake of the antimicrobial to achieve the maximum therapeutic benefit of the treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, low-frequency (20 kHz-1 MHz) and lowintensity (20-1000 mW/cm 2 ) ultrasound (LFLIU) is a safe and promising debridement and antibacterial treatment (9,10). The bactericidal effect of LFLIU alone is low, but combined with antibiotics can produce a synergistic bactericidal effect, whether on planktonic bacteria or bacterial biofilms (11)(12)(13). The stable cavitation of LFLIU generated numerous channels on the bacterial membrane and the extracellular matrix of biofilm that promoted the rapid entry of antibiotics into the bacteria, thus significantly increasing the effective concentration of antibiotics.…”
Section: Introductionmentioning
confidence: 99%